PENGARUH PENDAPATAN ASLI DESA (PAD), DANA DESA (DD), ALOKASI DANA DESA (ADD) TERHADAP BELANJA DESA BIDANG PENDIDIKAN DENGAN JUMLAH PENDUDUK MISKIN SEBAGAI VARIABEL MODERASI - Muslikah, Sitiana; Sulistyo, Sulistyo; Mustikowati, Rita Indah (Fakultas Ekonomi Universitas Kanjuruhan Malang, 2020)
This study aims to examine and explain how the influence of village income, village funds, allocation of village funds to village spending in education with the number of poor people as a moderating variable. The number of samples was 12 villages where the researchers took 5 years of the APBDes budget, namely the 2015-2019 fiscal year, and the researchers used a non-purposive sampling method. The variables used by researchers are original village income, village funds, allocation of village funds as an independent variable, village expenditure in education as the dependent variable, and the number of poor people as a moderating variable. The results of the analysis conducted by researchers conducted using SPSS silmutan produce village original income, village funds, allocation of village funds significantly influence village spending in education, partially original village income and allocation of village funds have no significant effect on education spending in the village field, while village funds have a significant influence on village expenditure in education and the population strengthens the influence of village original income, village funds, allocation of village funds to education spending in the field of education.